Capital structure determinants in the context of listed family firms - Vieira, Elisabete Simões
This paper provides an analysis of the capital structure in the context of Portuguese listed family firms, covering the period from 1999 to 2010. Using a panel data approach, we find that family controlled firms differ from non-family firms in several aspects. Family firms use more debt than non-family firms and have a lower proportion of independent directors. In addition, they finance new projects with debt financing and are sensitive to the cost of debt and the crisis periods, whereas non-family firms with higher levels of cash have more debt financing. Overall, we find a negative relationship between profitability and non-debt tax shield and debt and a positive relationship between firms’ age and debt.